Neoliberal Globalization and Senior High School: Insights from Public Schools in Negros Oriental, Philippines - Simporios, Lloyd Lyndel (Journal of learning theory and methodology (Online), 2025)
Objectives. This study explores how neoliberal globalization has shaped the implementation of the senior high school (SHS) program in the province of Negros Oriental, Philippines, focusing on its impact on students, educators, and the education system as a whole. Materials and methods. The study gathered insights through interviews and document analysis using a qualitative approach. The participants included 30 public school teachers and/or administrators and 30 public senior high school students. They shared their experiences and perspectives by understanding how global economic policies influence local educational practices. Results. The findings reveal that while the SHS program aims to prepare students for a competitive global economy, its implementation reflects neoliberal ideals such as privatization and market-driven skills. These changes have created challenges in ensuring equitable access and quality education, particularly for marginalized communities. Conclusions. This study underscores the need for educational reforms that meet global standards while remaining inclusive and responsive to the needs of local communities. By addressing these gaps, the education system can better serve its stakeholders and foster equitable opportunities for all.